Jarring witnesses : modern fiction and the representation of history - Holton, Robert, 1950- (New York : Harvester Wheatsheaf, 1994)
"Jarring Witnesses begins by surveying the problem of point of view as a formal, cognitive and cultural determinant in narrative historiography, particularly in the way certain dominant forms of 'legitimate' history have necessitated the suppression of the voices of 'jarring witnesses'. The problem is explored in relation to Pierre Bourdieu's theories of doxa and heterdoxy, Bakhtin's concept of heteroglossia, and postmodernism. With this theoretical framework established, a number of modern novels concerned with history are then explored. Chapters devoted to Conrad's Nostromo, Ford's Parade's End, and Faulkner's Absalom, Absalom! examine the ultimately orthodox historiographical points of view in these novels, while a chapter on the fiction of African-American women engages the problem of historiography from the margins of the dominant culture. In the final chapter, Pynchon's V is the focus of a discussion of postmodernism and historical discourse." "This is an original, interdisciplinary work which engages issues of contemporary academic debate and illustrates its arguments with examples from well-known texts. The book is relevant to current debates in the problems of narrative representation both in fiction and the writing of history, while addressing questions being raised in literary studies concerning the representation of cultural difference and the varieties of social and discursive power."--BOOK JACKET.
pt. 1. History and narrative: Historical narrative and the politics of point of view -- Common sense and historical narrative -- pt. 2. Modernism and orthodoxy: Nostromo and the "torrent of rubbish" -- Parade's end: "Has the British this or that come to this!" -- Absalom, Absalom!: the "nigger in the woodpile" -- pt. 3. Postmodernism and heterodoxy: Bearing witness: African-American women's fiction -- V: in the rathouse of history with Thomas Pynchon.
"Earlier versions of chapters 6 and 7 have appeared in Textual practice and English studies in Canada"--Title page verso.
"First published 1994 by Harvester Wheatsheaf ... Hemel Hempstead, Hertfordshire"--Title page verso.
Includes bibliographical references (pages 280-296) and index.
Second ISBN from label with bar code on p. [4] of cover.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Conrad, Joseph; Fiction -- 20th century -- History and criticism; Literature and history; History in literature; Historiography; Postmodernism (Literature); Littérature et histoire; Histoire dans la littérature.; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Fiction; History in literature; Literature and history; Geschichtsdarstellung; Historischer Roman; Geschichtsbild; Roman; USA; Romans; Geschiedschrijving; Representatie (algemeen); Literature - General; Languages & Literatures; Littérature -- Histoire et critique; Historiographie; Postmodernisme et littérature.; Geschichte 1900-1990.; Englisch; Fiction -- 20th century -- History and criticism; Literature and history; History in literature; 1900-1999; English fiction; Criticism, interpretation, etc